Design and synthesis of irreversible inhibitors of foot-and-mouth disease virus 3C protease. - Roqué,Rosell NR; Mokhlesi,L; Milton,NE; Sweeney,TR; Zunszain,PA; Curry,S; Leatherbarrow,RJ (Bioorg Med Chem Lett, 2014)
Foot-and-mouth disease virus (FMDV) causes a highly infectious and economically devastating disease of livestock. The FMDV genome is translated as a single polypeptide precursor that is cleaved into functional proteins predominantly by the highly conserved viral 3C protease, making this enzyme an attractive target for antiviral drugs. A peptide corresponding to an optimal substrate has been modified at the C-terminus, by the addition of a warhead, to produce irreversible inhibitors that react as Michael acceptors with the enzyme active site. Further investigation highlighted key structural determinants for inhibition, with a positively charged P2 being particularly important for potency.